2021
DOI: 10.3389/fmicb.2020.623574
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of Non-carbapenemase Producing Carbapenem-Resistant Enterobacterales in South Texas

Abstract: BackgroundCarbapenem-resistant Enterobacterales (CRE) pose a significant global public health threat. Resistance among CRE is particularly complex, owing to numerous possible resistance mechanisms and broad definitions. We aimed to characterize the clinical and molecular profiles of CRE in the South Texas region.Materials and methodsWe compared the clinical, genotypic, and phenotypic profiles of carbapenemase producing Enterobacterales (CPE) with those of non-carbapenemase producers (NCPE) isolated from South … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 18 publications
1
20
1
Order By: Relevance
“…Several studies have also reported that K. pneumoniae and KPC-producing CRE are pre-dominant in the U.S. [ 4 , 13 , 28 ]. These findings are contrary to a recent study, which reported that 43% of CRE cases were K. pneumoniae followed by 27% E. coli and 30.3% being KPC-producing CRE [ 29 ]. This contradictory finding may be due to the small sample size of that study, which included only 42 cases (43%) of K. pneumoniae .…”
Section: Discussioncontrasting
confidence: 98%
“…Several studies have also reported that K. pneumoniae and KPC-producing CRE are pre-dominant in the U.S. [ 4 , 13 , 28 ]. These findings are contrary to a recent study, which reported that 43% of CRE cases were K. pneumoniae followed by 27% E. coli and 30.3% being KPC-producing CRE [ 29 ]. This contradictory finding may be due to the small sample size of that study, which included only 42 cases (43%) of K. pneumoniae .…”
Section: Discussioncontrasting
confidence: 98%
“…A more recent study assessing the clinical and genomic epidemiology of carbapenem-resistant Enterobacterales in the United States ( 3 ) showed that Houston was the first major city in the United States where carbapenem-resistant K. pneumoniae CG307 seemed to have established endemicity along with isolates belonging to CG258. Furthermore, a recent study suggests that CG307 may be spreading to other municipalities in South Texas and cocirculating with CG258 ( 31 ). The concomitant circulation of these major clones provided an opportunity to dissect their dynamics of dissemination, genetic relationships, and evolution using a pangenomic approach combined with clinical data.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons underlying the high prevalence of non-CP isolates in our bacteremia cohort are not currently known but may include relatively stringent infection control practices amongst our highly immunocompromised patients. Recently, Black et al noted a higher prevalence of non-CP-CRE (59%) in south Texas where non-CP-CRE patients were more likely to receive a longer duration of antibiotic treatment as well as more likely to have an emergency department visit compared to CPE albeit with low number of observations (39). This finding is consistent with our cancer patient population that receives a high level of antibiotic treatment (40) and coincides with the finding that previous antibiotic exposure has been identified as a risk factor for non-CP-CRE relative to CPE in other studies (7).…”
Section: Discussionmentioning
confidence: 99%